2014
DOI: 10.3174/ajnr.a4149
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Modern Stroke Thrombectomy Approaches Using an In Vitro Cerebrovascular Occlusion Model

Abstract: BACKGROUND AND PURPOSE:A new in vitro cerebrovascular occlusion model of the intracranial circulation was developed recently for testing thrombectomy devices. Using this model, we compared recanalization success associated with different modern endovascular thrombectomy approaches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(43 citation statements)
references
References 14 publications
2
41
0
Order By: Relevance
“…In an in vitro study the rate of EDT reached 13%, which is similar to the rates reported in the ADAPT and ADAPT FAST studies 20. In the in vitro study, although clot removal via ADAPT tended to be more efficient for reducing large fragments (200–1000 μm), ADAPT led to high numbers of distal emboli in the size ranges of 100–200, 50–100, and <50 μm 15…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In an in vitro study the rate of EDT reached 13%, which is similar to the rates reported in the ADAPT and ADAPT FAST studies 20. In the in vitro study, although clot removal via ADAPT tended to be more efficient for reducing large fragments (200–1000 μm), ADAPT led to high numbers of distal emboli in the size ranges of 100–200, 50–100, and <50 μm 15…”
Section: Discussionsupporting
confidence: 81%
“…An in vitro vascular model has also shown that a stent retriever and traditional aspiration thrombectomy result in fragmentation of the embolus during extraction, creating downstream emboli and, potentially, emboli to previously uninvolved vascular territories 15 19 20…”
Section: Discussionmentioning
confidence: 99%
“…There have been reports of a few in vitro studies concerning which delivery system provides the highest recanalization rate with the lowest incidence of ENT/EDT. 3,4) In this study, we reviewed past cases treated at our institution and compared the therapeutic results between groups treated with BGC alone and in combination with DAC. The time from puncture to recanalization was significantly shorter in the BGC + DAC group (p = 0.03).…”
Section: Resultsmentioning
confidence: 99%
“…23 Balloon guide catheters can be used to halt anterograde blood flow in the affected vascular territory and serve to reduce distal embolization during thrombectomy attempts, although their utility is currently debated. 12,35,37,47,52 In addition, BGCs have been reported as a primary means for aspiration thrombectomy in proximal occlusions. 17 Currently, the Penumbra aspiration catheters (Penumbra, Inc.) are the only catheters approved by the FDA for aspiration thrombectomy, and their use has resulted in TICI Grade 2b/3 in 57%-84% of cases.…”
Section: Aspiration Devicesmentioning
confidence: 99%